Multidisciplinary approach for the treatment of a complicated crown-root fracture in a young patient: A case report - de Castro, José Carlos Monteiro [UNESP]; Poi, Wilson Roberto [UNESP]; Pedrini, Denise [UNESP]; Tiveron, Adelisa Rodolfo Ferreira [UNESP]; Brandini, Daniela Atili [UNESP]; de Castro, Mara Antônio Monteiro [UNESP] (My University, 2011)
Crown-root fractures in permanent teeth cause esthetic and functional problems. This paper reports the case of a complicated crown-root fracture in the maxillary right central incisor of a young patient who was treated with a multidisciplinary approach in two phases. A modified Widman flap, root canal therapy, glass fiber post cementation, and adhesive tooth fragment reattachment were performed shortly after an accident. Satisfactory esthetic and functional outcomes were obtained. However, the patient did not attend follow-up visits and returned after 7 years. During this second phase, the clinical and radiographic examination showed stability and adaptation of the fragment and good periodontal health conditions, but crown darkening and a radiolucent image associated with the root apex of the fractured tooth were also observed. The periapical lesion was surgically removed by apicoectomy, and the esthetics were recovered with a direct composite resin veneer on the traumatized tooth. © 2011 by Quintessence Publishing Co Inc.
Keywords: Dental bonding; Patient care planning; Tooth fractures; Tooth injuries